Pendiri di Dewan Direksi dan Kinerja Perusahaan yang Dimoderasi Koneksi Politik dan Kepemilikan Keluarga - Jurnali, Teddy; Vonny, Vonny (E-Jurnal Akuntansi; Vol 33 No 3 (2023), 2023)
This study aims to examine the role of founders on the board of directors on the performance of companies with family ownership and political connections as moderating variables. The determination of the research sample used purposive sampling from companies listed on the Indonesia Stock Exchange (IDX). The number of samples used was 265 companies with a research time span of 2017-2021. Testing using panel regression using Eviews software. The results of the study show that the presence of the founder on the board of directors significantly influences the success of the company. The moderating variable of family ownership strengthens the relationship between founders on the board of directors and company performance, while political connections cannot moderate the relationship between founders on the board of directors and company performance. Keywords: Founders on Board of Director; Family Ownership; Political Connection; Firm Performance